Number of lymph nodes assessed has no prognostic impact in node-negative rectal cancers after neoadjuvant therapy. Results of the "Italian Society of Surgical Oncology (S.I.C.O.) Colorectal Cancer Network" (SICO-CCN) multicentre collaborative study. Issue 8 (August 2018) - Degiuli, Maurizio; Arolfo, Simone; Evangelista, Andrea; Lorenzon, Laura; Reddavid, Rossella; Staudacher, Carlo; De Nardi, Paola; Rosati, Riccardo; Elmore, Ugo; Coco, Claudio; Rizzo, Gianluca; Belluco, Claudio; et al.
Abstract: Introduction: We retrospectively investigated the impact of number or complete absence of nodes retrieved on survival of patients with rectal cancer (RC) treated with neoadjuvant radiation-therapy (NAT). Methods: All patients with RC treated with NAT followed by curative surgery from 2000 to 2014 in 14 Italian referral Centres for Colorectal Surgery were enrolled. Information about number of nodes harvested, node ratio, type of radiation therapy schedule and tumour stage were recorded. Impact of number or complete absence of nodes retrieved on overall survival (OS) and on cumulative incidence of death for disease (CIDD) was assessed and factors influencing node yield were investigated. Results: In total, 1407 patients were included. Mean number of nodes retrieved was 12.9, while no lymph nodes were found in only 32 patients (2%, ypNnull). Definite nodal stage was ypN0 in 1001 patients (71%) and ypN+ in 372 patients (27%). In multivariable analysis ypNnull patients showed worse OS and CIDD compared to both ypN0 and ypN+. In ypN0 patients, number of nodes assessed, stratified in 4 groups (<5, 5–10, 11–15 and > 15), did not significantly influence OS and CIDD. Long-course radiation schedule and early T stages negatively affected node assessment. Conclusion: Complete absence of nodes assessed was associated with worse prognosis compared to node-negative and node-positive patients. In node-negative patients number of nodes was not associated to OS and CIDD. Based on data from this large population of irradiated RC, number of nodes assessed has no prognostic impact in node-negative patients.